2011
DOI: 10.1089/omi.2010.0094
|View full text |Cite
|
Sign up to set email alerts
|

Urine Metabolomic Analysis Identifies Potential Biomarkers and Pathogenic Pathways in Kidney Cancer

Abstract: Kidney cancer is the seventh most common cancer in the Western world, its incidence is increasing, and it is frequently metastatic at presentation, at which stage patient survival statistics are grim. In addition, there are no useful biofluid markers for this disease, such that diagnosis is dependent on imaging techniques that are not generally used for screening. In the present study, we use metabolomics techniques to identify metabolites in kidney cancer patients' urine, which appear at different levels (whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(122 citation statements)
references
References 22 publications
6
112
1
3
Order By: Relevance
“…15 We performed a pilot "fast track" study using several complementary separation techniques (which cover most of the metabolome) and showed that urine analysis can separate patients with earlystage RCC from control patients who do not have RCC. 2 An extension of that study demonstrated significant changes in quinolinate, 4-hydroxybenzoate, and gentisate (at a false discovery rate of 0.26), 16 an interesting finding because these metabolites are involved in common pathways of specific amino acid and energetic metabolism, consistent with high tumor protein breakdown and utilization, and the Warburg effect. 17 Furthermore, grade dependent analysis of urine metabolites showed differential urinary concentrations of several acylcarnitines as a function of both cancer status and kidney…”
Section: Techniques Of Metabolomics Analysismentioning
confidence: 81%
“…15 We performed a pilot "fast track" study using several complementary separation techniques (which cover most of the metabolome) and showed that urine analysis can separate patients with earlystage RCC from control patients who do not have RCC. 2 An extension of that study demonstrated significant changes in quinolinate, 4-hydroxybenzoate, and gentisate (at a false discovery rate of 0.26), 16 an interesting finding because these metabolites are involved in common pathways of specific amino acid and energetic metabolism, consistent with high tumor protein breakdown and utilization, and the Warburg effect. 17 Furthermore, grade dependent analysis of urine metabolites showed differential urinary concentrations of several acylcarnitines as a function of both cancer status and kidney…”
Section: Techniques Of Metabolomics Analysismentioning
confidence: 81%
“…The purpose of the first part of the present study was to investigate the amino acid content in the urine of patients suffering from prostate carcinoma and to compare the results with the urine samples of the controls obtained from healthy individuals. Previously, it was reported that metabolism of amino acids is perturbed in tumor cells (24,25), and urine amino acid profiles are consistently altered during tumor development (20,26,27).…”
Section: Resultsmentioning
confidence: 99%
“…Recent metabolomics studies have revealed new facets of cancer biology that have opened avenues to novel chemotherapeutic strategies and molecular diagnostic techniques, identifying metabolic dysregulation caused by malignant transformation (e.g., 2-hydroxyglutarate in brain, blood-borne and colorectal tumors [37][38][39], quinolinate in renal cell carcinoma [40], and sarcosine in prostate and colorectal cancer [10,39]). Since the initial demonstration that sarcosine abundance is associated with prostate cancer aggressiveness, several investigators have worked to determine how best to apply metabolomics in cancer diagnosis and patient management, reviewed in Refs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified molecular signatures of prostate cancer that are associated with aggressive disease [10,35,36]. Measurement of these molecular patterns from minimally invasive biological samples (biofluids or biopsy tissue collected in the course of conventional patient management) is anticipated to provide clinically actionable information that better individualizes cancer patient care.Recent metabolomics studies have revealed new facets of cancer biology that have opened avenues to novel chemotherapeutic strategies and molecular diagnostic techniques, identifying metabolic dysregulation caused by malignant transformation (e.g., 2-hydroxyglutarate in brain, blood-borne and colorectal tumors [37][38][39], quinolinate in renal cell carcinoma [40], and sarcosine in prostate and colorectal cancer [10,39]). Since the initial demonstration that sarcosine abundance is associated with prostate cancer aggressiveness, several investigators have worked to determine how best to apply metabolomics in cancer diagnosis and patient management, reviewed in Refs.…”
mentioning
confidence: 99%